Topographical analysis of machined surfaces after grinding with different cooling-lubrication techniques - Ruzzi, Rodrigo de Souza; Ribeiro da Silva, Leonardo Rosa; Silva, Rosemar Batista da; Silva Junior, Washington Martins da; Bianchi, Eduardo Carlos [UNESP] (Elsevier B.V., 2020)
The search for more sustainable grinding processes resulted in alternative cooling-lubrication techniques, as minimum quantity lubrication (MQL). However, this shift changes the associated tribosystem and, thus, the surface topography. This work investigates the topography of SAE 4340 steel after grinding with different cooling-lubrication techniques: flood, MQL and MQL with cleaning system (MQL + CS). The topography was analyzed through several roughness parameters and SEM. The results showed that surfaces ground with the MQL and MQL + CS presented larger bearing areas and lower peaks and valleys dispersion. The MQL technique, especially the MQL + CS, also lowered the grinding wheel wear by better cleaning the wheel pores. Furthermore, the CS was efficient at removing debris that adhered to the wheel and improved lubrication of the tribosystem.
Keywords: Topographical characterization; Grinding; Roughness parameters; MQL technique